A Configuration Management Model for Software Product Line - Yu, Liguo; Ramaswamy, Srini (INFOCOMP Journal of Computer Science, 2006)
Software Product Line has proved to be an effective approach to benefit from software reuse. Configuration management, an integral part of any software development activity, takes on a special significance in software product line context. This is due to the special property of software product line, in which the core assets are shared by all products. In this paper, we compare the existing configuration management models and analyze the artifacts that need to be configuration managed in software product line. We then present an evolution-based configuration management model for software product line, in which, the configuration management is divided into two domains, the production domain and the product domain. In this model, the evolution propagation of corrective changes and enhancement changes on different configuration artifacts follow different paths. The advantages and the constraints of this model are also discussed.